Between individual and collective social effort: vocabularies of informed citizenship in different information environments - Gagrčin, Emilija; Porten-Cheé, Pablo (International journal of communication, 2023)
Information disorder and digital media affordances challenge informed citizenship as an ideal and in practice. While scholars have attempted to adapt the normative ideal to contemporary changes and challenges by introducing new metaphors and normative benchmarks, this study investigates citizens’ ideals and practices of informed citizenship by deploying the concept of citizenship vocabularies. Drawing on interviews with citizens from different information environments—Germany and Serbia—we offer a conceptual outline of informed citizenship as an individual and collective social effort. Our findings illustrate the role of the information environment in shaping citizenship vocabularies. We advance the idea of informed citizenship as a relational practice, arguing for a social ontological approach to theorizing informed citizenship today.